REFLECTING THE PERCENTAGE OF SENTENCE TYPES IN EFL STUDENTS’ PARAGRAPH WRITING ASSIGNMENTS: A DESCRIPTIVE STUDY ON PEDAGOGICAL OUTCOMES OF LEARNING ENGLISH WRITING - Syayid Sandi Sukandi (Universitas Negeri Padang, 2017)
This research quantitatively presents and reflects findings on the percentage of Indonesian EFL students’ sentences in their writing assignments that were submitted online in Writing 1 course. Each type of sentences is coded differently: Simple Sentence (Code: S.S.), Compound Sentence (Code: C.S.1), Complex Sentence (Code: C.S.2), and Compound-Complex Sentence (Code: C.C.S). Each of these types of sentences is measured along with their occurrences in students’ paragraph writing on five genres. Percentage on type of sentences is analysed through quantitative measurement. Samples of this research are 10% from all population, which is specifically seen through the number of students’ writings submitted online. The result of this research shows five obvious occurrences. For S.S. type, students used it mostly in descriptive genre with 32.58% from total sentences written in the descriptive genre. For C.S.1 type, students used it mostly in descriptive genre with 39.44% from total sentences written in the descriptive genre. For C.S.2 type, students mostly used it in argumentative genre with 34.42% from total sentences written in the argumentative genre. For C.C.S type, students mostly used it in comparison-contrast genre with 30.26% from total sentences written in the comparison-contrast genre. This finding reveals that pedagogically, awareness on students’ writing product in learning English writing should be less important than looking at students’ writing process in the same type of learning.